Caracterización morfológicas de Hongos micorrízicos arbúsculares en fincas de cinco Cantones, de la Provincia De Los Ríos - Cabrera León, Roddy Iván (2020)
For a long time, work has been done worldwide, with the aim of demonstrating the importance of mycorrhizal fungi within agricultural production systems. Said works have been based on the physiological, morphological and especially taxonomic part of these fungi. However, these works have not been able to cover all the producing areas of the country, and many have not been fully disseminated. Researchers have made very commendable efforts to put this information on technical personnel working in the fields of Ecuador. However, despite these initiatives, it is still difficult to know how much has been covered. The present work seeks to collect all the information generated by various means and to generate a roadmap from the results of the analyzes carried out by the producers. The results show a fairly limited diversity in the reported species of mycorrhizae for the five areas evaluated in the province of Los Ríos. In addition, the populations found show a low regenerative capacity of the fungi and spore populations, due in many cases to the incessant workload and applications of agrochemicals that normally occur in crops. This suggests that there must be a change in the way farmers work, since, in some way, food production must be guaranteed through having healthy and highly productive soils, taking care of the microbiota.